2012
DOI: 10.1088/0004-637x/745/2/176
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Epoch of Reionization: Limitations From Foreground Confusion and Imaging Algorithms

Abstract: Tomography of redshifted 21 cm transition from neutral Hydrogen using Fourier synthesis telescopes is a promising tool to study the Epoch of Reionization (EoR). Limiting the confusion from Galactic and Extragalactic foregrounds is critical to the success of these telescopes. Instrumental response or the Point Spread Function (PSF) of such telescopes is inherently 3 dimensional with frequency mapping to the Line of Sight (LOS) distance. EoR signals will necessarily have to be detected in data where continuum co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
286
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(288 citation statements)
references
References 11 publications
2
286
0
Order By: Relevance
“…This relationship, known colloquially as "the wedge," was derived analytically (P12b; Vedantham et al 2012;Thyagarajan et al 2013;Liu et al 2014aLiu et al , 2014b, and has been confirmed in simulations (Datta et al 2010;Hazelton et al 2013) and observationally Dillon et al 2014). As described in P12b, the wedge is the result of the delay between when a wavefront originating from foreground emission arrives at the two antennas in a baseline.…”
Section: Calibrationmentioning
confidence: 69%
“…This relationship, known colloquially as "the wedge," was derived analytically (P12b; Vedantham et al 2012;Thyagarajan et al 2013;Liu et al 2014aLiu et al , 2014b, and has been confirmed in simulations (Datta et al 2010;Hazelton et al 2013) and observationally Dillon et al 2014). As described in P12b, the wedge is the result of the delay between when a wavefront originating from foreground emission arrives at the two antennas in a baseline.…”
Section: Calibrationmentioning
confidence: 69%
“…The shape of the multi-baseline modemixing ripple is different in each uv pixel and depends on the details of the foregrounds and on the exact locations of the baselines contributing to each location, but unlike the mode mixing discussed in previous work Trott et al 2012;Vedantham et al 2012;Parsons et al 2012), the spatial frequency (k ) of this ripple is not limited by the field of view of the instrument so it can throw power into higher k modes, including into the EoR window.…”
Section: Multi-baseline Simulationmentioning
confidence: 95%
“…The lowest k mode shown is the flat-spectrum (k = 0) mode, which would contain all the foreground power if there were no mode mixing. Our simulations naturally include the single-baseline effects identified by Morales et al (2012), Trott et al (2012), Vedantham et al (2012), and Parsons et al (2012) because we form visibilities as described in Equation (1), but we find that the multi-baseline effects dominate the mode-mixed power throughout the uv plane. The contamination that is present in the EoR window is a signature of multi-baseline mode mixing which can produce contamination to arbitrarily high k .…”
Section: Power Spectramentioning
confidence: 99%
“…It is worth noting that the gridding scheme presented here for the delay-spectrum technique differs substantially for other schemes that have been recently presented in the literature (e.g., Bowman et al 2009;Vedantham et al 2012) in that within an 8 MHz sub-band, every frequency channel has been formed from the same weighted sum of constituent baselines. .…”
Section: Gridding and Integrationmentioning
confidence: 99%